Concentrations of trace elements in a rare and threatened coastal shark from the Arabian Gulf (smoothtooth blacktip Carcharhinus leiodon). Issue 2 (30th November 2015) - Moore, Alec B.M.; Bolam, Thi; Lyons, Brett P.; Ellis, Jim R.
Highlights: We analysed trace elements in a rare shark found off Kuwait. Concentrations of several elements were remarkably high, including mercury and lead. Mercury concentrations exceeded European limits for safe human consumption. We confirm pollution as an additional stressor for this rare, threatened species. Abstract: Kuwait's waters are one of only two locations where the smoothtooth blacktip shark Carcharhinus leiodon is known to occur. Concentrations of 11 trace elements were analysed in five juvenile and two adult specimens of this coastal predator. Concentrations of lead in muscle increased with length, whilst manganese concentration decreased. Arsenic concentrations in muscle were among the highest reported in elasmobranchs, and the concentration in the liver increased significantly in relation to length. In comparison to published literature, concentrations of manganese (liver), lead (muscle) and iron (muscle and liver) were high. Mercury concentrations in the muscle exceeded European Food Safety Authority limits and were among the highest reported in any elasmobranch. Concentrations of selenium, which may inhibit mercury toxicity, were also high. These results and previous studies indicate that potentially hazardous levels of mercury and other contaminants may occur in sharks in this region, adding further stressors to these vulnerable populations.